2018
DOI: 10.5812/jjcdc.66417
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis G Virus and Co-Infection with Hepatitis B Virus and Hepatitis C Virus Among Hemodialysis Patients in Ahvaz, Iran

Abstract: Background: Patients on hemodialysis are at a high-risk for acquiring blood-borne infections, such as hepatitis G, hepatitis C, and hepatitis B viruses. The aim of this investigation was to determine the prevalence of HGV infection among patients on hemodialysis and its co-infection with hepatitis C and B viruses in Ahvaz. Methods: Blood samples were collected from patients on hemodialysis during January to July, 2016. RNAs were extracted from sera and cDNA was prepared using the kit. The nested-polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
4
2
0
Order By: Relevance
“…Many studies have reported that the duration of hemodialysis was a risk factor for GBV-C infection supporting patient-to-patient transmission (Hasan et al, 2018;Sanchooli et al, 2018), which is consistent with the current study finding. This could be attributed to nosocomial infections as a result of hemodialysis units failure to adhere to strict infection control procedures.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Many studies have reported that the duration of hemodialysis was a risk factor for GBV-C infection supporting patient-to-patient transmission (Hasan et al, 2018;Sanchooli et al, 2018), which is consistent with the current study finding. This could be attributed to nosocomial infections as a result of hemodialysis units failure to adhere to strict infection control procedures.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, GBV-C was found in 35 (35%) of hemodialysis patients, 17 (35.4%) of whom were HCV positive and 18 (34.6%) were HCV negative, Table (2). This prevalence is within the range reported in other countries including Indonesia (55%) (Handajani et al, 2000), Germany (50%) (Sanchooli et al, 2018), Turkey (25%) (Akcali et al, 2006), Italy (24%) (De Filippi et al, 2001), Iran (10%) (Sanchooli et al, 2018), and Pakistan (3.6%) (Qureshi et al, 2020). Variable rates of blood transfusion, surgical procedure and adherence to universal precautions may explain these disparities in GBV-C prevalence.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the current study, GBV-C was found in 35 (35%) of hemodialysis patients, 17 (35.4%) of whom were HCV positive and 18 (34.6%) were HCV negative, Table (2). This prevalence is within the range reported in other countries including Indonesia (55%) (Handajani et al, 2000), Germany (50%) (Sanchooli et al, 2018), Turkey (25%) (Akcali et al, 2006), Italy (24%) (De Filippi et al, 2001), Iran (10%) (Sanchooli et al, 2018), and Pakistan (3.6%) (Qureshi et al, 2020). Variable rates of blood transfusion, surgical procedure and adherence to universal precautions may explain these disparities in GBV-C prevalence.…”
Section: Discussionsupporting
confidence: 67%
“…Variable rates of blood transfusion, surgical procedure and adherence to universal precautions may explain these disparities in GBV-C prevalence. The variation in GBV-C prevalence around the world could be attributed to variation in amplified target region and primers used (Sanchooli et al 2018). In Iraq, the rate of GBV-C infection among healthy people was 0%, hemodialysis was 20.3%, and thalassemia was 14.8% (Hasan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%